Reference dosimetry of proton pencil beams based on dose-area product: a proof of concept. (22nd May 2017) - Gomà, Carles; Safai, Sairos; Vörös, Sándor
Abstract: This paper describes a novel approach to the reference dosimetry of proton pencil beams based on dose-area product ( D A P w ). It depicts the calibration of a large-diameter plane-parallel ionization chamber in terms of dose-area product in a 60 Co beam, the Monte Carlo calculation of beam quality correction factors—in terms of dose-area product—in proton beams, the Monte Carlo calculation of nuclear halo correction factors, and the experimental determination of D A P w of a single proton pencil beam. This new approach to reference dosimetry proves to be feasible, as it yields D A P w values in agreement with the standard and well-established approach of determining the absorbed dose to water at the centre of a broad homogeneous field generated by the superposition of regularly-spaced proton pencil beams.